2010
DOI: 10.3390/e12020275
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization during Friction in Complex Surface Engineered Tribosystems

Abstract: Self-organization during friction in complex surface engineered tribosystems is investigated. The probability of self-organization in these complex tribosystems is studied on the basis of the theoretical concepts of irreversible thermodynamics. It is shown that a higher number of interrelated processes within the system result in an increased probability of self-organization

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
172
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(176 citation statements)
references
References 14 publications
(29 reference statements)
4
172
0
Order By: Relevance
“…The values δX n and δJ n are fluctuations of the corresponding flows and forces in steady-state conditions. In [21] it is shown that as the number of interacting thermodynamic flows increases the probability of a loss of thermodynamic stability of the tribosystem increases. Hence, the probability of self-organization grows.…”
Section: The Physical Meaning Of the Self-organization Phenomenon As mentioning
confidence: 99%
“…The values δX n and δJ n are fluctuations of the corresponding flows and forces in steady-state conditions. In [21] it is shown that as the number of interacting thermodynamic flows increases the probability of a loss of thermodynamic stability of the tribosystem increases. Hence, the probability of self-organization grows.…”
Section: The Physical Meaning Of the Self-organization Phenomenon As mentioning
confidence: 99%
“…Friction and wear reduction due to protective tribofilm [12][13]22,25,[31][32][33][34] Slip waves Elastic waves at the interface which can result in friction reduction. Can result in selforganized critical behavior and stick-slip.…”
Section: Future Directionsmentioning
confidence: 99%
“…To a large extent, they continued the research of the Kiev group, in particular, in the theory of -tribological compatibility‖ of materials, and the synergetic action of the electric current during the current collection, as well as wear resistant composite metallic coatings for heavily loaded cutting tools. Their results, which employ extensively the concept of entropy, were summarized in the monograph edited by Fox-Rabinovich and Totten [12]. In 2002, N. Bushe won the most prestigious tribology award, the Tribology Gold Medal, for his studies of tribological compatibility and other related effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multilayered coatings may have lower hardness, but possess enhanced wear resistance properties [9,10]. Such type of nanostructured coatings exhibit adaptive behavior during operation through generation of tribofilm on the friction surface, that allows protecting and lubricating the surface and, as a result, allows decreasing of the wear rate [11].…”
Section: Introductionmentioning
confidence: 99%